2011
DOI: 10.1177/1934578x1100600604
|View full text |Cite
|
Sign up to set email alerts
|

Solid State Structure and Absolute Configuration of Filifolinol Acetate

Abstract: Careful reevaluation of the 1 H and 13 C NMR spectroscopic data of filifolinol acetate (4) led to the reassignment of the C-10 and C-11 signals, as well as the gem-dimethyl signals. Single crystal X-ray analysis provided an independent structural confirmation of 4, and comparison of the experimental vibrational circular dichroism spectrum with calculations performed using density functional theory provided the absolute configuration of this 3H-spiro-1-benzofuran-2,1'-cyclohexane and related molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The absolute conguration of the revised structure (as depicted below) was determined using VCD and DFT (B3LYP/ DGDZVP) calculations for the diacetate derivative. 154 The absolute conguration of the algal meroditerpenoids (À)-taondiol diacetate (132) and (+)-epitaondiol diacetate (133) was determined by VCD and DFT calculations (B3LYP/DGDZVP and B3LYP/DGDZVP2, respectively). 148 The previous erroneous assignments were based on the ECD helicity rule for the chromane chromophore, 149 which was shown to be invalid for the title molecules aer theoretical calculations of ECD spectra.…”
Section: Meroterpenesmentioning
confidence: 99%
“…The absolute conguration of the revised structure (as depicted below) was determined using VCD and DFT (B3LYP/ DGDZVP) calculations for the diacetate derivative. 154 The absolute conguration of the algal meroditerpenoids (À)-taondiol diacetate (132) and (+)-epitaondiol diacetate (133) was determined by VCD and DFT calculations (B3LYP/DGDZVP and B3LYP/DGDZVP2, respectively). 148 The previous erroneous assignments were based on the ECD helicity rule for the chromane chromophore, 149 which was shown to be invalid for the title molecules aer theoretical calculations of ECD spectra.…”
Section: Meroterpenesmentioning
confidence: 99%
“…[17] Thus, the so called steric approach control, a term coined by Dauben, [18] and further developed in the torsional strain model proposed by Fehlkin and Ahn, [19] would allow us to obtain the stereoisomer with the hydroxyl group in axial position as observed in the X-ray structure of Filifolinol Acetate. [20] Recently however, it has been shown that although the use of small nucleophiles tends to add to the axial face, some six-membered cyclic ketones suffered the hydride addition from the equatorial face even when a small hydride reagent such as sodium borohydride (NaBH 4 ) is used. [21] With this in mind, three bulky hydride reagents, -H, LiAlH(t-BuO) 3 and NaBH(OCOCH 3 ) 3 in order to favor the equatorial approach of the hydride to the carbonyl compound were used.…”
Section: Resultsmentioning
confidence: 99%
“…This structure was assigned using NMR and single crystal X-ray analysis, and its absolute configuration was determined as 2S,9S,12R using VCD and DFT (B3LYP/DGDZVP) calculations. [20] At late stage of the synthesis, examination of literature reports involving synthesis of spirodihydrobenzofurans, showed that only a few methodologies to carry out the key spiroannulation reaction have been reported. For example, in the total synthesis of K-76 ( Figure 3), a fungal metabolite isolated from Stachybotrys complementi nov. sp, [27] and one of the most widely used complement inhibitors, [10] the spirocyclization reaction was achieved using a THF-ethylene glycol-2.0 N hydrochloric acid mixture.…”
Section: Resultsmentioning
confidence: 99%
“…73 . One glycerol unit can be replaced by a branched nonitol (calditol) ( 314 ). These compounds can also be found in geological specimens ( 315 ).…”
Section: Glycerol Ethers From Archaebacteria and Sedimentsmentioning
confidence: 99%
“…The absolute configuration of filifolinol acetate (282) was determined by VCD methodology using DFT at the B3LYP/DGDZVP level of theory (314). The atomic coordinates from its X-ray structure were used as a starting point for the conformational search using the MMFF force field.…”
Section: Example 11mentioning
confidence: 99%